PENDEKATAN DESAIN ARSITEKTUR INDISCHE DALAM PERANCANGAN PASTORAN GEREJA SANTO ANTONIUS KOTABARU DI YOGYAKARTA - Sinta Dewi; Sushardjanti Felasari; Yoseph Duna Sihesa; Samsul Hasibuan (Jurnal Arsitektur ARCADE, 2022)
Abstract: Being located in the centre of cultural heritage area of Kotabaru, city of  Yogyakarta,  the Saint Anthony Catholic Church then is known as Kotabaru Church (Dutch: Nieuw Wijk Katholieke Kerk). The church is located in Abu Bakar Ali street (Boulevard Jonquiere) and I Dewa Nyoman Oka street (Sultansboulevard). As one of the eldest churches in the city, the church was built during the colonial time and inaugurated in 1926 by Mgr. A. Van Velsen SJ, the Bishop of Jakarta. In 2014 The Saint Anthony Church was stated as a cultural heritage building. In October 2016 the Church bought a piece of land with a building on it, adjacent to its parish house. The two story building was half constructed, developed from a single story Indische architectural style building which unfortunately was already destroyed, leaving only a small part of its original building entrance. The building was planned to be functioned as the new parish house with a spatial connection to the old parish house. Despite the strong recommendation to reduce the expenses by making minimum physical changes, the building especially the façade should be redesigned as far as possible to be restored to its original façade and according to the requirements as an Indische architectural style building. As a part of the cultural heritage buildings in the area of Kotabaru, the new parish house should perform contextual architectural style and elements. Furthermore, the design results are proposed three alternatives and presented in the form of floorplans and elevations.Abstrak: Terletak di tengah kawasan cagar budaya Kotabaru, Kota Yogyakarta, Gereja Katolik Santo Antonius kemudian dikenal dengan nama Gereja Kotabaru (Bahasa Belanda: Nieuw Wijk Katholieke Kerk). Gereja tersebut terletak di Jalan Abu Bakar Ali (Boulevard Jonquiere) dan Jalan I Dewa Nyoman Oka (Sultansboulevard). Sebagai salah satu gereja tertua di kota Yogyakarta, gereja ini dibangun pada masa kolonial dan diresmikan pada tahun 1926 oleh Mgr. A. Van Velsen SJ, Uskup Jakarta. Pada tahun 2014 Gereja Santo Antonius ditetapkan sebagai bangunan cagar budaya. Pada bulan Oktober 2016 Gereja membeli sebidang tanah dengan sebuah bangunan di atasnya, bersebelahan dengan rumah parokinya. Bangunan berlantai dua ini setengah dibangun, dikembangkan dari bangunan bergaya arsitektur Indische berlantai satu yang sayangnya sudah hancur, hanya menyisakan sebagian kecil dari entrance bangunan aslinya. Gedung tersebut rencananya akan difungsikan sebagai rumah paroki baru dengan keterkaitan spasial dengan rumah paroki lama. Meskipun ada rekomendasi kuat untuk mengurangi biaya dengan melakukan perubahan fisik seminimal mungkin, bangunan terutama fasad harus didesain ulang sejauh mungkin untuk dikembalikan ke fasad aslinya dan sesuai dengan persyaratan sebagai bangunan bergaya arsitektur Indische. Sebagai bagian dari bangunan cagar budaya di wilayah Kotabaru, rumah paroki baru hendaknya menampilkan gaya dan elemen arsitektur yang kontekstual. Selanjutnya, hasil rancangan diusulkan 3 alternatif dan disajikan dalam bentuk denah dan tampak bangunan.